2017
DOI: 10.2147/ott.s150071
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of pristimerin on human osteosarcoma cells in vitro and in vivo

Abstract: There are very few treatments for musculoskeletal tumors, compared to other cancers; thus, novel therapeutic drugs are needed. Pristimerin (PM) is a triterpene compound isolated from plant extracts that reportedly has antitumor effects on various cancers, such as of the breast and prostate. The purpose of this study was to evaluate the antitumor effects of PM on human osteosarcoma cells. Treatment of the human osteosarcoma cell lines, MNNG and 143B, with PM led to a dose-dependent decrease in cell viability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…PM has been reported to have anti-tumor effects on human breast and lung cancer cells (21). We have previously shown that PM has an anti-tumor effect on human osteosarcomas (22). In the present study, PM exhibited a concentration-and time-dependent inhibition of cell viability in human fibrosarcoma cells.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…PM has been reported to have anti-tumor effects on human breast and lung cancer cells (21). We have previously shown that PM has an anti-tumor effect on human osteosarcomas (22). In the present study, PM exhibited a concentration-and time-dependent inhibition of cell viability in human fibrosarcoma cells.…”
Section: Discussionsupporting
confidence: 64%
“…Wu et al, reported that the IC50 values for human breast cancer cell lines, MCF-10A and MDA-MB-231, were 1.4-1.6 and 0.5-0.6 µM, respectively, after 24 h of PM administration and 1.0-1.2 and 0.4-0.6 µM, respectively, at 48 h. Wu et al, also reported that the IC50 values for human lung epithelial carcinoma cells, A549 and human liver cancer cell lines, HepG2 and Hep3B, were 0.4-0.6 µM at 72 h of PM administration (21). Mori et al, reported that the IC50 value for human osteosarcoma cell lines, MNNG and 143B, were 0.8-0.9 and 0.5-0.6 µM, respectively, at 24 h of PM administration, and 0.3-0.4 and 0.3-0.4 µM, respectively, at 48 h. Meanwhile, the IC50 values for human osteoblasts were reported to be ≥0.5 µM, at both 24 and 48 h of PM administration (22). In this study, The IC50 values for human fibrosarcoma cells were 0.16 µM at 24 h of PM administration, and 0.13 µM at 48 h of PM administration, whereas the IC50 values for human fibroblasts were 0.59 µM at 24 h of PM administration, and 0.32 µM at 48 h post PM administration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…the intrinsic (mitochondrial) pathway that activates caspases 9 and 3 via cytochrome C release from mitochondria, and the extrinsic (death receptor) pathway that activates caspases 8 and 10 through receptors (so-called "death receptor") present on the cell membrane surface [37]. In a recently study, Pristimerin induced elevation of caspase 3 and activation of upstream caspases 8 and 9 [38]. When Pristimerin induced apoptosis, it was in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…The antiproliferative activity of pristimerin goes beyond colon-related cancers, it is extended to breast [346][347][348][349][350], melanomas [351], osteosarcoma [352], pancreatic [353,354], and prostate cancers [355][356][357][358]. Herein, we describe a few examples focusing on articles that have demonstrated potential mechanisms of action.…”
Section: Pristimerinmentioning
confidence: 99%